Students Perception of Gamified Learning in EFL Class : Online Quizizz for Engagement and Motivation - Fahada, Nazli; Asrul, Nurmahyuni (Journal Of Education And Teaching Learning (JETL), 2024)
This study investigated gamified learning, particularly online quizizz, in EFL (English as a Foreign Language) One digital educational game that is gaining popularity is quizizz, a game-based online test that enables entertaining multiplayer teaching activities and allows learners to practice with their devices. This study aimed to examine students' perceptions of the use of quizizz on student motivation and engagement. A descriptive quantitative research design was used in this study, in which data were collected from questionnaires to gain insight into how quizizz affected the aspects of motivation and  engagement. The questionnaire data were analyzed using descriptive statistics. The study found that quizizz significantly increased students' motivation to learn English, with the interactive nature of the platform being a key factor in boosting their enthusiasm for language learning. Despite a minority of respondents finding quizizz boring, the majority reported enjoying the platform's gamified approach to learning and felt more active and engaged during classes where quizizz was utilized. Additionally, participants acknowledged quizizz's substantial contribution to their knowledge of English vocabulary and grammar. Moreover, the study found that quizizz positively shaped students' perceptions of online learning, its potential to enhance digital learning experiences and enhance student engagement in english learning. The findings underscore the beneficial effects of quizizz on student motivation and engagement.